La dificultad de ser amado - Rodríguez, Pablo Uriel (ARFIL y UNL, 2018)
Nowadays, Works of Lave is one of the most read books by Kierkegaard’s scholars. Since Theodor Adorno published his critics to Kierkegaard’s theory of love, the usual readings has focused on the subject of love (Christian lover) and has forgotten the object of love (neighbor). I consider that is important to think a new question: how does the neighbor experiment Christian love? To answer this question, this paper revisits mains concepts of Honneth’s theory of recognition. I will try to show two hypothesis: i) from human point of view, Kierkegaard’s conception of Christian love is not a superior form of recognition, and ii) the Singular only needs God to develop his self.